2023
DOI: 10.1002/cam4.6191
|View full text |Cite
|
Sign up to set email alerts
|

Blood and saliva‐derived ctDNA is a marker of residual disease after treatment and correlates with recurrence in human papillomavirus‐associated head and neck cancer

Abstract: BackgroundThere is an alarming increase in human papillomavirus‐associated head and neck cancer (HNC), reaching epidemic levels. While patient prognosis is generally good, off‐target treatment effects are associated with decreased quality of life. Thus, non‐invasive strategies to predict treatment response and risk of recurrence could help de‐escalate treatment. In this study, we tested circulating tumor (ct)DNA in liquid biopsies (blood/saliva) of HPV‐positive HNC patients to assess treatment response and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Looking first at the individual sensitivities, specificities, PLRs, NLRs, and DORs of salivary ctHPV DNA in detecting all OP cancers, a notable trend arises. Values derived from Ferrier et al were the strongest, whereas those from Wang et al were the lowest values relative to all studies. This suggests upgrades in testing technology following their publication may have enhanced detective accuracy—a theory supported by Brooks et al having the second highest DOR and second most recent publication date.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Looking first at the individual sensitivities, specificities, PLRs, NLRs, and DORs of salivary ctHPV DNA in detecting all OP cancers, a notable trend arises. Values derived from Ferrier et al were the strongest, whereas those from Wang et al were the lowest values relative to all studies. This suggests upgrades in testing technology following their publication may have enhanced detective accuracy—a theory supported by Brooks et al having the second highest DOR and second most recent publication date.…”
Section: Discussionmentioning
confidence: 56%
“…Brooks et al demonstrated the highest sensitivity with a value of 88% (95% CI, 40%-99%). Ahn et al and Ferrier et al shared the highest specificity results, but the former study had a slightly narrower CI at 97% (95% CI, 90%-99%) compared with the latter’s 97% (95% CI, 88%-99%). The pooled sensitivity and specificity across all studies were 64% (95% CI, 36%-85%) and 89% (95% CI, 46%-99%), respectively.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“… 14 In cervical cancer, HPV (human papilloma virus) ctDNA was found to be a marker for early detection of relapse and residual disease. 15 , 16 , 17 Nevertheless, the genetic variants in ctDNA associated with the response to NACT in LACC patients are still unexplored.…”
Section: Introductionmentioning
confidence: 99%